Pennisetum alopecuroides 'Weserbergland' 'Weserbergland' Fountain Grass - Edward Gilman (EDIS, 2007)
This document provides an overview of the ‘Weserbergland’ dwarf cultivar of fountain grass, scientifically known as Pennisetum alopecuroides 'Weserbergland’. It describes the plant’s characteristics, including its height, spread, and growth habits. The grass features white, bottle brush-like inflorescences that persist into fall and bright green foliage that turns golden brown in autumn. It is noted for its fine texture and graceful fountain shape, making it suitable for mass planting, containers, and borders. The document also covers its planting requirements, such as full sun and well-drained soils, and mentions its high drought tolerance and pest resistance. Additionally, it highlights the plant’s ornamental value and provides guidance on propagation through division. Original publication date October 1999.